Evaluating the Results According to Simulations to Improve Power Control and Enhance Optical Communication Performance - Zeki Mohammed, Dunya; Abdulmunem Kadhim Hammadi (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
In this paper, an experimental study has been conducted to detail power-control optimization in wavelength-division multiplexed (WDM) optical communication systems by use of Erbium-Doped Fiber Amplifiers (EDFAs). Our study shows that adaptive power control can greatly improve the performance of the system with a superb 35.7% improvement of the maximum power capacity relative to traditional constant power schemes. Throughout its study, the paper uses elaborate simulations to determine the bit-error rate (BER), signal-to-noise ratio (SNR), and energy efficiency of the different modulation formats, such as QPSK and 16-QAM. Findings suggest that adaptive power control has the potential to conserve as much as 50 percent of power in various data rates, with QPSK modulation presenting a better result in power-constrained conditions. We have also tried several optimization algorithms, such as gradient descent and more sophisticated ways of learning to adapt, like Adam, and found that there is indeed a strong advantage in the number of steps to converge with high precision. We have demonstrated that intelligent power management is important in improving both the performance and energy efficiency of optical networks, which is the future of more sustainable communication solutions.